Intra-abdominal cystic lymphangioma of the mesocolon sigmoids: a rare entity in adult patient woman - Guachilema Ribadeneira, Alex (J Surg Case Rep, 2020)
The lymphangioma is a benign neoplasm, mostly connate, it occurs more often in children. It is more frequently located in the head–neck region, as well as in the armpit, and less frequently in the abdomen. The diagnosis, as well as their appearance is variant, they can be asymptomatic depending on the size. The signs on the physical exam are usually nonspecific and can look like an acute abdomen. Imaging tests used are the ultrasound and tomography, which determine the therapeutic behavior. The differential diagnosis should be made with other intra-abdominal injuries, such as cavernous hemangioma, mesotheliomas, pancreatic and ovarian tumors and even peritoneal hydatid cyst. The definitive treatment is surgical in most cases, with complete excision of the mass. The definitive diagnosis is obtained with the histopathological study of the surgical piece.